Problem-based learning: an interdisciplinary approach in clinical teaching - Mohamed, N.H.; Abdul Kadir, R. (2005)
A review of the dental curriculum in 1994 at the Faculty of Dentistry, University of Malaya paved way for a five-year programme to replace the four-year curriculum that had been in existence since the faculty was set up in 1972. The new curriculum saw many changes in the mode of teaching which included an interdisciplinary approach particularly in clinical teaching. This provided the impetus for problem-based learning to be included. Such an approach came in the form, among others, of an integrated seminar in the fifth year of dental education which was scenario-based and saw the inclusion of various teaching disciplines in dentistry. The objective of the problem-based learning approach was to develop and promote critical and analytical thinking skills of dental students in the university’s effort to improve their decision making ability. In so doing, students in small groups were expected to learn to work together to identify learning issues from real-life situations, develop skills to resource and critically analyzed appropriate and relevant materials and subsequently, came to a consensus of the ‘best’ method to manage the issues at hand. The learning process was enhanced with the presence of faculty staffs taking the role of facilitators. Assessment of the final year students showed that they perform better as clinicians through the use of this mode of teaching.